Estado de la investigación del uso de fibras orgánicas e inorgánicas para el diseño de hormigones autorreparables - Burgos Campuzano, Cynthia Alexandra (2024)
This research work is based on a bibliographic review of high-impact articles published in the last five years in databases such as Scopus and Science Direct, with the aim of finding the most recent findings regarding the development of the use of organic and inorganic fibers as precursor compounds for the self-healing capacity of concrete. The articles were filtered with the use of the Connected Papers tool. After analyzing these documents, the characteristics of each fiber were evident, and the impact that each of them has on the different mechanical properties of the concrete was contrasted; consequently, it was determined that the fibers mentioned above contribute to the durability and repair of concrete elements. A qualitative study was conducted by compiling the results obtained by different authors based on the comparisons of resistances achieved by investigating control samples and samples with mixtures of fibers and additional substances tested after the repair of injuries. This information aims to broaden knowledge about using different fibers to extend the useful life of concrete while preserving its resistance and reducing the cost of maintenance. Thus, it optimizes the use of resources and reduces the manufacture of such a polluting material as concrete and its compounds.